Chemerin suppresses murine allergic asthma by inhibiting CCL2 production and subsequent airway recruitment of inflammatory dendritic cells. Issue 6 (23rd April 2014) - Zhao, L.; Yang, W.; Yang, X.; Lin, Y.; Lv, J.; Dou, X.; Luo, Q.; Dong, J.; Chen, Z.; Chu, Y.; He, R.
Abstract Background Chemerin has been implicated to play opposing roles, either pro‐inflammatory or anti‐inflammatory, in various tissue inflammation processes primarily through the regulation of tissue recruitment of immune cells. However, the effect of chemerin in allergic asthma has not yet been explored. We sought to investigate the role of chemerin in the murine model of allergic asthma and explore the underlying mechanism. Methods We examined the effect of intranasal (i.n.) administration of chemerin during antigen challenge in murine models of asthma. Moreover, we examined whether administration of CCL2 or bone marrow‐derived dendritic cells (BMDCs) transfer reversed the effects of chemerin on ovalbumin‐induced asthma. We finally examined the effect of chemerin on CCL2 expression in activated lung epithelial cells in vitro. Results The administration of chemerin attenuated allergic airway inflammation and airway hyperreactivity during antigen challenge. Chemerin treatment caused significant decreases in BALF CD4+ T‐cell accumulation and mRNA expression of Th2‐attracting chemokines, CCL17 and CCL22, which was accompanied by significantly decreased BALF CD11c+CD11b+ inflammatory DC accumulation and CCL2 production. Furthermore, airway administration of exogenous CCL2 or adoptive transfer of CD11c+CD11b+ BMDCs abrogated the suppressive effects of chemerin on allergic asthma. Finally, in vitro study showed that chemerin inhibited CCL2 secretion by low‐dose LPS‐stimulated lung epithelial cells, which led to decreased chemotaxis of BMDCs. Conclusions Our study demonstrates that chemerin plays a protective role in allergic asthma by suppressing airway recruitment of inflammatory CD11c+CD11b+ DCs through the inhibition of CCL2 secretion by active lung epithelial cells.